2015
DOI: 10.1186/s13063-015-1080-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iodine supplementation in pregnancy on early childhood neurodevelopment and clinical outcomes: results of an aborted randomised placebo-controlled trial

Abstract: BackgroundConcern that mild iodine deficiency in pregnancy may adversely affect neurodevelopment of offspring has led to recommendations for iodine supplementation in the absence of evidence from randomised controlled trials. The primary objective of the study was to investigate the effect of iodine supplementation during pregnancy on childhood neurodevelopment. Secondary outcomes included pregnancy outcomes, maternal thyroid function and general health.MethodsWomen with a singleton pregnancy of fewer than 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 21 publications
(27 reference statements)
1
56
0
1
Order By: Relevance
“…Further randomized controlled trials are clearly desirable here, however key problems exist. A recent trial ended prematurely due to unforeseen cessation of funding as the Australian government initiated a recommendation that iodine supplements should be routinely used by all pregnant women. Trials of iodine supplementation in women with mild‐moderate iodine deficiency may now no longer be ethically viable with regard to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Further randomized controlled trials are clearly desirable here, however key problems exist. A recent trial ended prematurely due to unforeseen cessation of funding as the Australian government initiated a recommendation that iodine supplements should be routinely used by all pregnant women. Trials of iodine supplementation in women with mild‐moderate iodine deficiency may now no longer be ethically viable with regard to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 30 years, National Health and Nutrition Examination Survey (NHANES) showed that there is a decreased of 50% in the iodine intake [16]. The Japan and China are the countries that have lowest world rate of perinatal mortality because one of sources iodine intake is through of seaweed and the women intake a big quantity of seaweed compared to other women of the world [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Seaweed has a capacity of accumulated most iodine that sea water, however the distance from the sea also influences the iodine content of plants, how much major the distance, lower the concentration of iodine [18].…”
Section: Discovery Of Iodine and Use In The Medicinementioning
confidence: 99%
“…Besides, the ability of perspire is coordinated by iodine and patients with cancer has difficulty perspiring due to iodine deficiency in the skin. Increase of various types of cancer is linked with iodine deficiency, minerals and vitamins that are lacking in the sun as selenium and magnesium [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Survival rates of cancer are the same as those of the last 70 years [21] even with all the advances like mammograms, surgery, chemotherapy and radiotherapy.…”
Section: Strong Evidence On Iodine Intakementioning
confidence: 99%
See 1 more Smart Citation
“…There is a sustained debate on the ethical implications of a randomised controlled trial of iodine supplementation in pregnancy, in parallel with concerns over the adverse effects of salt and the conflicted message that salt iodisation would convey [20,21]. There are a range of other strategies to tackle iodine insufficiency, including updating dietary recommendations, introducing mandatory salt fortification, and new nutritional education strategies aiming to increase awareness and promote iodine rich foods [22,23].…”
Section: Introductionmentioning
confidence: 99%